Serological diagnosis and post-treatment monitoring of Echinococcus granulosus in experimentally infected dogs using crude and recombinant fibronectin antigens - Celik, Figen; Selcuk, Muhammed Ahmed; Uslug, Muhammet; Simsek, Sami (Elsevier, 2025)
Echinococcus granulosus is a zoonotic helminth responsible for cystic echinococcosis, a significant public health concern. The diagnosis of E. granulosus infections in definitive hosts, such as dogs, is challenging due to the absence of clinical signs. This study aimed to evaluate the diagnostic performance of crude (EgSCA) and recombinant (rEgFN162) antigens for the detection of E. granulosus infection in dogs using ELISA and Western blot assays. Additionally, it sought to identify the most suitable antigen and method for population-based screening and post-treatment monitoring. Adult E. granulosus parasites were collected from experimentally infected dogs using arecoline hydrobromide purgation. Soluble crude antigen (EgSCA) was prepared through freeze-thaw cycles, sonication, and filtration, while recombinant fibronectin protein (rEgFN162) was obtained via gene cloning, expression, and purification in E. coli. The antigenic properties of EgSCA and rEgFN162 were analyzed by SDS-PAGE and Western blot. ELISA assays were performed to assess IgG and IgM responses in experimentally infected and treated dogs. Based on IgG ELISA results, EgSCA showed a sensitivity of 96.66 % and specificity of 66.66 %, while rEgFN162 demonstrated a sensitivity of 76.66 % and specificity of 46.66 %. In Western blot analysis, EgSCA achieved a sensitivity of 90 % and specificity of 83.33 %, whereas rEgFN162 showed 66.66 % sensitivity and 73.33 % specificity. The recombinant antigen showed a higher ability to differentiate E. granulosus infections from other helminth infections. The findings suggest that rEgFN162 is a promising candidate for the serodiagnosis of E. granulosus in dogs, with potential applications in epidemiological studies and post-treatment follow-up. Further validation with larger sample sizes is needed to confirm its diagnostic accuracy in natural infections.
Keywords: Echinococcus granulosus; Fibronectin; Crude antigen; Dog; Serodiagnosis; Western blot; ELISA